Synthesis, antimicrobial and antifungal activity of 3-(2-bromophenyl)-5-(alkylthio)-4-phenyl-4H-1,2,4-triazoles - A. A. Safonov; O. I. Panasenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
To select a molecule that could become a promising pharmacological agent, chemists use already-known heterocyclic bases by adding pharmacologically active groups. One such heterocyclic system is 1,2,4-triazole base, on the basis of which a huge number of biologically active compounds have already been found. It is known that 1,2,4-triazole derivatives show a fairly high antimicrobial and antifungal effect while remaining low-toxic compounds and 5-alkylthio-1,2,4-triazoles exhibit antimicrobial and antifungal activity. Based on the literature search, it can be concluded that 3-(2-bromophenyl)-5-(alkylthio)-4-phenyl-4H-1,2,4-triazoles are insufficiently studied.